Coarse-grained molecular dynamics study of elasticity of block copolymers with cubic symmetrical morphology. (14th March 2022) - Aoyagi, Takeshi
Abstract: In the present study, we investigated the elasticity of block copolymers by coarse-grained molecular dynamics simulation. We focused on two typical cubic symmetry morphologies that mimic thermoplastic elastomers and soft plastics—i.e., body-centered cubic (BCC) and double gyroid (DG). The effects of morphology, bridge fraction, and deformation direction on the stress–strain curves were studied. The deformation of glassy networks with the DG morphology resulted in higher initial moduli than those with the BCC morphology. With the BCC morphology, the rubber elasticity was linearly dependent on the bridge fraction, whereas with the DG morphology the dependency was weak because the loop configuration in the DG networks also contributed to rubber elasticity. In both the BCC and DG morphologies, the effect of deformation direction was insignificant. This was inconsistent with the experimental results. The discrepancy demonstrates the peculiar nature of the coarse-grained bead-spring model in the glassy state. Graphical abstract: Image 1 Highlights: Rubber elasticity of spherical morphology is proportional to bridge fraction. Bridge fraction of double gyroid morphology less contributes to rubber elasticity. Double gyroids with glassy network show considerably initial high modulus. Shortcomings of coarse-grained molecular dynamics in glassy state are revealed.